PENINGKATAN KETERAMPILAN MEMBACA SISWA KELAS III MENGGUNAKAN MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) SD NEGERI 29 GANTIANG UTARA PADANG - Yetty Morelent; Yulisna, Risa (Cerdas Proklamator, 2023)
The lack of use of learning models that are attractive to students is one of the factors causing the low reading ability of students in class, especially elementary school students. This research aims to improve students' reading skills using the Cooperative Integrated Reading and Composition (CIRC) model for class III students at SDN 29 Gantiang Utara Padang. This type of research is classroom action research with a qualitative and quantitative approach. Research procedures are planning, implementation, observation and reflection. The research subjects were 26 class III students who carried out two cycles. Research data is in the form of objective tests and observation results from all actions. Observation and test data collection techniques. The research results increased students' reading skills learning outcomes in cycle I by 65.3%, this was because many students were not able to read correctly and fluently. Meanwhile, in cycle II there was an increase of 77%, because the learning implementation process was appropriate. From the research results it can be concluded that learning Indonesian using the Cooperative Integrated Reading and Composition (CIRC) model can improve the reading skills of class III students at SD Negeri 29 Gantiang Utara Padang.